MECHANICAL BEHAVIOR OF FLOWING CONCRETE AND EARLY STRENGTH CONCRETE WITH THE ADDITION OF TYPE D AND F ADMIXTURES - Chairunnisa, Nursiah; Pratiwi, Ade Yuniati; Syahputera, Muhammad Syarif; Nurwidayati, Ratni (Journal of Applied Engineering Science, 2022)
Flowing concrete (FC) and self-compacting concrete (SCC) that are produced with admixtures can be a solution to the complexity of construction problems. Self-compacting concrete is a special type of flowing concrete, but flowing concrete is not necessarily self-compacting concrete. This paper investigates the adding type D and F admixtures with andesite stone as the potential local coarse aggregate materials which were abundantly available for flowing concrete and early strength concrete (ESC) performance. This study has two test categories: fresh concrete and hardened concrete. The fresh concrete category includes slump, slump flow, and T500 tests. Meanwhile, the hardened concrete category includes compressive, splitting tensile, and flexural strength tests. The experimental results indicated that the admixture type F dosage of 1.0%, 1.55% and 1.75% cement weight can enhance the compressive strength by 3.88%, 5.82% and 9.71% respectively. The combination of type F and D admixtures with dosage of 0.15% and 0.2% cement weight show a reduction in compressive strength by 12.62% and 3.89% respectively. On the other hand, both combination of admixtures can reach better performance on the final setting time which lead the slows the hydration process and provides adequate time to put concrete to the formwork. The results also show adequate correlations between compressive strength and the flexural strength. Furthermore, a prediction model is established the ratio of both value based on the regression analyses, while it decreases obviously with the increase of compressive strength. It can be clearly that the ratio is strongly affected by compressive strength.
Keywords: admixtures, retarder, flowing concrete, early strength concrete